Improving the Ability to Read Aloud Syllables and Words with Correct Pronunciation through the Problem Based Learning Model at MI Negeri 50 Bireuen - Nurjannah; Sri Hartati (MANDAILING GLOBAL EDUKASIA, 2025)
Syllables and words with correct pronunciation. This is shown by a low daily score, which does not meet the Minimum Competency (KKM). The Minimum Competency (KKM) required for the Indonesian (KD) curriculum Reading aloud syllables and words with correct pronunciation is 70, so students should get a score above 70. Yesterday, only 6 students, or 30%, achieved grades above the KKM; the rest undergo corrective actions to achieve higher grades. Based on the interviews, teachers took the initiative to use an unusual learning model in the classroom: problem-based learning. This class action research was conducted at MIN 50 Bireuen, in the first grade consisting of 20 students. The research population is all MIN 50 Bireuen students in the 2024/2025 academic year. Data collection techniques include test and non-test techniques. The results of the pre-cycle study showed that only 6 students (30%) achieved the graduation score (KKM = 70), while 14 students (70%) did not achieve the score. Therefore, the researcher seeks to improve the learning process in Cycle I by developing and developing a more comprehensive learning improvement plan. Based on the formative test scores after the improvement of Cycle I, learning outcomes have improved. This is shown by the increase in the scores of the formative test, from 6 students (30%) to 15 students (75%). The results of observations in Cycle II show that students actively participate in the learning process and carry out the teacher's duties effectively. The use of a problem-based learning model has been proven to be able to improve student learning outcomes as planned.